Smart Governance for Smart Societies: A Narrative Review of Digital Models - Fitriani (Indonesian Scientific Publication, 2025)
Digital governance has become an increasingly critical dimension of contemporary governance, integrating digital technologies into decision-making, service delivery, and stakeholder engagement. This narrative review aims to identify opportunities and challenges associated with digital governance across public and corporate sectors. A systematic literature search was conducted using Scopus, Web of Science, and Google Scholar, employing keywords such as digital governance, public administration digitalization, corporate governance digital era, and platform economy. Inclusion criteria prioritized peer-reviewed studies published in the last two decades that address the intersection of governance and digital transformation, encompassing both theoretical and empirical contributions. Findings reveal that digital technologies significantly enhance transparency, accountability, and efficiency through mechanisms such as open data, big data analytics, and artificial intelligence. Social media and digital platforms expand citizen participation and reshape administrative legitimacy, while corporate governance increasingly relies on artificial intelligence and data economics to strengthen accountability and sustainability. Smart cities illustrate the potential of digital governance in urban sustainability, though challenges remain regarding regulatory uncertainty and technological interoperability, particularly in the use of blockchain and NFTs. Despite these opportunities, disparities in infrastructure, digital literacy, and regulatory frameworks limit adoption in developing nations, reinforcing inequalities. The review concludes that robust policies, inclusive ecosystems, and cross-sector collaborations are essential to harness the benefits of digital governance. Future research should explore context-specific models and long-term implications to ensure that digital transformation advances inclusive, transparent, and resilient governance systems.